2018
DOI: 10.3389/fpls.2018.00674
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Different Hyperspectral Variables for Diagnosing Leaf Nitrogen Accumulation in Wheat

Abstract: Hyperspectral remote sensing is a rapid non-destructive method for diagnosing nitrogen status in wheat crops. In this study, a quantitative correlation was associated with following parameters: leaf nitrogen accumulation (LNA), raw hyperspectral reflectance, first-order differential hyperspectra, and hyperspectral characteristics of wheat. In this study, integrated linear regression of LNA was obtained with raw hyperspectral reflectance (measurement wavelength = 790.4 nm). Furthermore, an exponential regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Some authors have reported the close relationship among the indices with chlorophyll content [9]. In conjunction with a sampling field design, and a follow-up growing season practices program, they are a reliable alternative to estimate Nt to reduce cost and time in decision-making [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported the close relationship among the indices with chlorophyll content [9]. In conjunction with a sampling field design, and a follow-up growing season practices program, they are a reliable alternative to estimate Nt to reduce cost and time in decision-making [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate regression is a method used to measure the degree of linear relationship between multiple independent variables (predictors) and dependent variables (responses). While many different multivariate regression algorithms exist, PLSR has proven to be most robust for N measurement using high-dimensional hyperspectral data [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. In a preliminary analysis, we tested several well-accepted multivariate regression algorithms which have previously been used for N measurement in plants, including support vector machine regression [ 16 ] and stepwise regression [ 15 ], and found that PLSR achieved equal or better results.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, for comparison, some well-known vegetation indices (VIs) previously used to measure the N content of plants were tested using the spectrometer data. Tan, et al [ 10 ] compared 18 VIs using hyperspectral data and found that the normalised red edge area index (NREAI) proposed by Gong, et al [ 25 ] had the best correlation with the leaf N accumulation (LNA) of wheat. NREAI has the form of ( SD r − SD b )/( SD r + SD b ), where SD b is the integration of the first-order derivative values in the blue-edge covering 490 nm to 530 nm and SD r is the integration of the those in the red-edge from 670 nm to 737 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has great application potential in large-scale crop growth monitoring, crop yield estimation, agricultural monitoring and forecasting, and agricultural resources survey [14][15][16] . In China and abroad, considerable work has been done on remote sensing estimation of crops, and great progress has been made 17,18 . Based on moderate-resolution imaging spectroradiometer (MODIS) derived normalized difference vegetation index (NDVI) data, a global agricultural monitoring system for crop monitoring and yield forecasting was built 19 .…”
mentioning
confidence: 99%